2004
DOI: 10.1097/00001756-200404290-00005
|View full text |Cite
|
Sign up to set email alerts
|

Akt activity in Alzheimer’s disease and other neurodegenerative disorders

Abstract: Enzyme activities of the serine/threonine kinase Akt were compared in mid-temporal and mid-frontal cortices from Alzheimer's disease cases and matched controls. Activities (GSK-3alpha/beta fusion protein phosphorylation by immunoprecipitated Akt) were significantly increased in temporal cortex soluble fractions from Alzheimer's disease compared with non-disease controls and positive disease controls with another neurodegenerative disease. Temporal cortex soluble fraction Akt activities positively correlated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
101
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(112 citation statements)
references
References 12 publications
7
101
1
Order By: Relevance
“…Akt is downstream of phosphatidylinositol-3 kinase (PI3K) and inhibits the activity of GSK3β by phosphorylation at the Ser9 residue. The amount of activated Akt is increased in AD brains compared to normal aged controls (47)(48)(49). This finding suggests that GSK3β activity in AD brains is finely tuned by the opposing actions of several inhibiting and activating kinases.…”
Section: The Role Of Other Protein Kinases In Admentioning
confidence: 88%
“…Akt is downstream of phosphatidylinositol-3 kinase (PI3K) and inhibits the activity of GSK3β by phosphorylation at the Ser9 residue. The amount of activated Akt is increased in AD brains compared to normal aged controls (47)(48)(49). This finding suggests that GSK3β activity in AD brains is finely tuned by the opposing actions of several inhibiting and activating kinases.…”
Section: The Role Of Other Protein Kinases In Admentioning
confidence: 88%
“…In addition, several studies have shown that PI3K/Akt activation protected against Aβ neurotoxicity [27,40,50]. However, pathological studies showed elevated Akt activation in AD brains [14,32,34]. Since tau contains several Akt phosphorylation sites including Ser214, which together with its neighboring Thr212 forms the AT100 tau epitope that is highly specific in the paired helical filaments (PHFs) present in AD [18,28], elevated Akt activation may promote tau hyperphosphorylation in AD.…”
Section: Discussionmentioning
confidence: 99%
“…38,39 There have been many post-mortem brain studies showing decreases in key insulin signaling proteins in the brains of people with AD. [40][41][42][43] In addition, Talbot et al 44 showed an impaired response to insulin in post-mortem brain regions including the cerebellar cortex and hippocampal formation compared to healthy controls who did not have evidence of insulin resistance at peripheral tissues. 44 This study was critical to show a functional impairment in response to insulin in the CNS, but not necessarily the peripheral tissues, in people with cognitive impairment.…”
Section: Insulin Resistancementioning
confidence: 99%